Natural Pigments of Anthocyanin and Betalain for Coloring Soy-Based Yogurt Alternative - Sandra Dias; Elisabete M. S. Castanheira; A. Gil Fortes; David M. Pereira; M. Sameiro T. Gonçalves (Foods, 2020)
The aim of this work was to evaluate the color stability of betalain- and anthocyanin-rich extracts in yogurt-like fermented soy, in order to develop a preliminary understanding of how these pigments behave in this type of food system during storage for 21 days at 4 °C. Thus, the extracts of red beetroot, opuntia, hibiscus and red radish were integrated into the yogurt-like fermented soy in two different ways—directly after lyophilization, and encapsulated in nanosystems based in soybean lecithin—as this approach has never been used to further increase the value and potential of the dairy-free alternatives of yogurt-like fermented soy. The results showed that non-encapsulated betalain-rich extracts from red radish are the most promising for coloring yogurt-like fermented soy. However, encapsulated opuntia extracts can also be an alternative to supplement the soy fermented beverages with betalains, without changing significantly the color of the system but giving all its health benefits, due to the protection of the pigments by nanoencapsulation.